Adhesion receptors as therapeutic targets for circulating tumor cells - Li, Jiahe; King, Michael R. (Frontiers in Oncology, 2012)
Metastasis contributes to >90% of cancer-associated mortality. Though primary tumors can be removed by surgical resection or chemo/radiotherapy, metastatic disease is a great challenge to treatment due to its systemic nature. As metastatic “seeds”, circulating tumor cells (CTCs) are believed to be responsible for dissemination from a primary tumor to anatomically distant organs. Despite the possibility of physical trapping of CTCs in microvessels, recent advances have provided insights into the involvement of a variety of adhesion molecules on CTCs. Such adhesion molecules facilitate direct interaction with the endothelium in specific tissues or indirectly through leukocytes. Importantly, significant progress has been made in understanding how these receptors confer enhanced invasion and survival advantage during hematogenous circulation of CTCs through recruitment of macrophages, neutrophils, platelets, and other cells. This review highlights the identification of novel adhesion molecules and how blocking their function can compromise successful seeding and colonization of CTCs in new microenvironment. Encouraged by existing diagnostic tools to identify and isolate CTCs, strategic targeting of these adhesion molecules to deliver conventional chemotherapeutics or novel apoptotic signals is discussed for the neutralization of CTCs in the circulation.